A Study of Topology Characteristics on the Real Deployment of Wireless Sensor Networks - Jaganathan, M.; Krishnan, V. R.; Zakaria, Mohd Sharim; Ahmad, Mohd Riduan (2010)
This paper investigates the effects of three parameters on the power consumption of sensor motes namely transmit power, frequency channel and sampling rate. Two wireless sensor network (WSN) test-beds have been deployed with two different types of topology; distributed and centralized. The WSN test-beds are built by using Crossbow IRIS motes where the effects of both real indoor and outdoor environment are investigated. Two different scenarios are considered which are line of sight (LOS) and non-LOS for both scenarios. In the case of centralized WSN with star topology, we discovered an interesting finding that the various transmit powers (ranging from 3.2dBm to -17dBm) do not vary the consumed power or in other word, the consumed powers across various transmit powers are almost the same for a given fixed distance value. The only parameter that affects the power consumption is the sampling rate. By increasing the rate, we can reduce the power consumption significantly. In the case of distributed WSN, we discovered that both transmit power and sampling rate affect the power consumption. The transmit power must be reduced and the sampling rate must be increased in order to save power in distributed WSN.